On retaining a multi-module floating structure in an amplitude death state. (15th July 2016) - Xia, S.Y.; Xu, D.L.; Zhang, H.C.; Qi, E.R.; Hu, J.J.; Wu, Y.S.
Abstract: A floating structure, consisting of multi-modules connected by flexible connectors, can be viewed as a network. Its response could evolve into a suppressed weak oscillatory state, referred as amplitude death (AD), desirable for system stability. In general, the AD state cannot persist when wave condition changes, usually leaping to large oscillations. In this paper, we put forward an adaptive method to maintain the floating structure in the stationary state by tuning the connector stiffness in variable wave conditions. The stiffness is determined by an optimization process based on a semi-analytical solution of the response of the floating structure. Numerical simulations are illustrated to verify the feasibility and effectiveness of the method. Highlights: A novel connector with adjustable stiffness is proposed. A new concept of amplitude death (AD) for stability design of VLFS is introduced. An adaptive method for maintaining the motion of VLFS in AD state is proposed. The method can be widely used in VLFS coupled with the other kind of connectors.